2008
DOI: 10.1159/000140671
|View full text |Cite
|
Sign up to set email alerts
|

Intrasplenic or Subperitoneal Hepatocyte Transplantation to Increase Survival after Surgically Induced Hepatic Failure?

Abstract: Background: As a basis for future clinical questions, we evaluated the efficacy of hepatocyte transplantation in a surgical model using a subperitoneal or intrasplenic approach for cell implantation. Methods: In rats, acute liver failure was induced by subtotal hepatectomy. Series of allogenic hepatocyte transplantations were performed by varying cell number, site, and sequence of cell transplantation. Results: Following subperitoneal or intrasplenic cell implantation subsequent to liver surgery, no survival b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…We have to identify the disease stages at which cell transplantation is effective to replace functional abnormalities of the hepatocytes without interfering with the altered hepatic architecture. There have been several studies testing different application sited for liver cell transplantation in rats and mice (Gabelein et al., 2008; Glanemann et al., 2009; Nagata et al., 2003a,b). Furthermore, we cannot exclude that transplanted NeoHepatocytes become cancerogenic after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…We have to identify the disease stages at which cell transplantation is effective to replace functional abnormalities of the hepatocytes without interfering with the altered hepatic architecture. There have been several studies testing different application sited for liver cell transplantation in rats and mice (Gabelein et al., 2008; Glanemann et al., 2009; Nagata et al., 2003a,b). Furthermore, we cannot exclude that transplanted NeoHepatocytes become cancerogenic after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“… 13 14 Recently, in another similar study, the average survival period after 90% resection was 3 days, and the survival rate 5 days after surgery was lower than 50%. 15 Another recent series showed that in acute liver failure models, 95% liver resection have been reported. 16 However, the mortality rate a short time after surgery was reported to be 80%, and thus this may not be a suitable model for investigating acute liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation may be that the hepatocytes in clinical studies were delivered into the splenic artery and not into the splenic pulp. This view is supported by Nagata and colleagues, who have shown that the route of hepatocyte delivery influences hepatocyte engraftment and function [18,53]. Another open question remains as to whether the human spleen is capable of accommodating a sufficient number of functional hepatocytes to compensate for the cirrhotic liver.…”
Section: Livermentioning
confidence: 94%
“…Tissue engineering After systemic application in animal models of hepatic intoxication and partial hepatectomy, myocardial infarction, nephropathy, cerebral ischemia, lung injury, lung fibrosis, and local irradiation, stem cells are enriched in injured tissue and partially differentiated into tissue-specific cell types [2,[17][18][19][20][21][22][23][24][25][26]. There have also been systemic applications of mesenchymal stem cells in humans with beneficial effect in graft-versus-host disease or osteogenesis imperfecta [27,28].…”
Section: Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation